(untitled) (Bangladesh Journal of Urology, 2025)
Prostatic utricle cyst resulting from Mullerian duct remnant is a rare congenital condition in males and is often associated with structural anomalies in external genitalia. While most cases remain asymptomatic, clinical presentation ranges from lower urinary tract voiding symptoms, urinary tract infection, epididymitis, rectal mass, hematospermia, and obstructive azoospermia. Transrectal ultrasound is the reliable modality of investigation to distinguish prostatic utricle cysts causing obstructive azoospermia, especially when complemented with characteristic semen analysis parameters. Magnetic resonance imaging is also beneficial when ultrasound is inconclusive. While vasography provides excellent information regarding anomalies in the reproductive tract, it should be performed when surgery is planned. Urethrocystoscopy remains one of the definitive approaches to diagnosing prostatic utricle cysts, and transurethral resection showed excellent outcomes while being minimally invasive. In this article, a rare case of obstructive azoospermia by prostatic utricle cyst is presented, and clinical symptoms, diagnosis, and management are discussed. Bangladesh J. Urol. 2024; 27(2): 146-150